Effects of twelve weeks of diabetes prevention program on cardiovascular risk factors - Thielen, Blaire (My University, 2019)
The purpose of this study was to generate hypotheses and measure the effectiveness of 12 weeks of Diabetes Prevention Program (DPP). The DPP, focused on increased physical activity, eating healthy, and portion control, was conducted looking specifically at how it affects cardiovascular disease risk factors. Participants from local exercise programs (n= 34) (>60 years of age), exercising a minimum of two days per week, meeting one of the following: BMI >25; fasting glucose of 100 to 125 mg/dl; hemoglobin A1c (HbA1c) of 5.7-6.4 mmol/L; > 9-point score on DPP questionnaire or a positive screening for prediabetes were included. Body weight, HbA1c, total cholesterol, LDL, HDL, triglycerides, BMI, FFM, body fat, SBP and DBP, PP, and waist circumference were measured pre and post completion of education sessions. Paired samples T test was used to determine statistical significance (p < .05). There was a significant decrease in HDL, weight, triglycerides, DBP, waist circumference, FFM and total cholesterol (P < 0.05). No significant difference was found in LDL, systolic blood pressure, BF, BMI, PP, or HbA1c.
Keywords: Diabetes; Cardiovascular system; Medicine, preventive; Kinesiology